Comparison of Efficacy between Tamsulosin and Finasteride on Symptomatic Benign Prostatic Hyperplasia (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jul;16(2): 154-159The abstract of this article is available on the PubMed website